PENGARUH DEBT TO EQUITY RATIO, PROFITABILITAS, KUALITAS AUDITOR DAN PERGANTIAN AUDITOR TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Desyana, Gita (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2019)
This study aims to find empirical evidence whether factors such as debt to equity ratio, profitability, auditor quality, and auditor turnover affect the compliance of manufacturing companies in the timely submission of financial statements on the Indonesia Stock Exchange.The data in this study are secondary data obtained from the company's annual financial statements in the Indonesian Stock Exchange (IDX). This type of research is ex post facto research. This research was conducted using a sample of 76 manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016-2018, so the research data analyzed amounted to 201. The data analysis technique used was descriptive statistics, multivariate test using logistic regression. Based on hypothesis testing, it can be concluded that overall, the companies that are on time are more numerous than the companies that are not on time in financial reporting to Bapepam. And the test results with logistic regression show empirical evidence that debt to equity ratio, profitability, auditor quality, and auditor turnover do not affect the timeliness of corporate financial reporting. Keywords : Debt To Equity Ratio, Profitability, Auditor Quality, Auditor Change And Timeliness.